A Recurrent Episode of Dermatomyositis Associated with Papillary Thyroid Cancer - Vijay Gopal Eranki (Case Reports in Endocrinology)
Objective. It is uncommon for dermatomyositis to be associated with papillary thyroid cancer. We report an unusual case of papillary thyroid cancer presenting with dermatomyositis. Methods. The case history, imaging and laboratory data is reviewed. Results. We report the case of a 62-year-old female with a prior history of dermatomyositis and breast cancer who presented with a recurrent episode of dermatomyositis. Extensive evaluation of the cause of the dermatomyositis recurrence revealed no recurrence of the breast cancer but a thyroid nodule was identified. The nodule was biopsied and the patient was noted to have papillary thyroid cancer. The patient subsequently underwent total thyroidectomy and had gradual improvement in her dermatomyositis. Conclusion. It is very uncommon for dermatomyositis to be associated with papillary thyroid cancer.